The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/mas.21692
|View full text |Cite
|
Sign up to set email alerts
|

Methods to improve quantitative glycoprotein coverage from bottom‐up LC‐MS data

Abstract: Advances in mass spectrometry instrumentation, methods development, and bioinformatics have greatly improved the ease and accuracy of site-specific, quantitative glycoproteomics analysis. Data-dependent acquisition is the most popular method for identification and quantification of glycopeptides; however, complete coverage of glycosylation site glycoforms remains elusive with this method. Targeted acquisition methods improve the precision and accuracy of quantification, but at the cost of throughput and discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 142 publications
0
11
0
1
Order By: Relevance
“…The general workflow of an MSn measurement consists of the isolation of the species and fragmentation of the precursor ions, followed by detection and data acquisition. Detailed reviews regarding MS approaches to glycomic and glycoproteomic analysis can be found elsewhere. ,,, Also, we note that data independent acquisition (DIA), despite being in its infancy, is an emerging technique to analyze glycopeptides; though we do not cover DIA here, we recommend recent reviews on the topic.…”
Section: Ms and Fragmentation Of Mucin-domain Glycoproteinsmentioning
confidence: 99%
“…The general workflow of an MSn measurement consists of the isolation of the species and fragmentation of the precursor ions, followed by detection and data acquisition. Detailed reviews regarding MS approaches to glycomic and glycoproteomic analysis can be found elsewhere. ,,, Also, we note that data independent acquisition (DIA), despite being in its infancy, is an emerging technique to analyze glycopeptides; though we do not cover DIA here, we recommend recent reviews on the topic.…”
Section: Ms and Fragmentation Of Mucin-domain Glycoproteinsmentioning
confidence: 99%
“…Such strategies can potentially be employed in the identification of DMPCs on membranes. Besides, the extraction methods of other proteins, such as total proteins, hydrophobic proteins, and glycoproteins, are also established and applied for proteomics studies 93 . Here, we summarized some solvents and commercial kits that are commonly used for different protein extraction in Table 2.…”
Section: Shotgun Proteomics Aim At Dmpc Detection Strategiesmentioning
confidence: 99%
“…In TIMS tunnel, an electric field is applied in an opposite direction to the drag of gas flow. The precursor ions are trapped at different positions based on the different CCS, then released consequentially to fragmentation or detection with the decreasing of electric field strength [34]. TIMS-MS has been successfully applied to analyze targeted peptides from biological samples [142].…”
Section: Characterization Of Glycopeptides Using Imsmentioning
confidence: 99%
“…The two main strategies for glycoproteomic analysis using MS are known as bottom-up and top-down approaches [29][30][31]. The bottom-up methodology uses proteolytic enzymes to digest glycoproteins in peptides and glycopeptides that are analyzed by MS; due the complexity of the data, the quantification needs to be addressed using computational tools [32][33][34]. In the top-down method, intact glycoproteins are directly analyzed in the MS system, thus enabling the identification of glycoproteins with minimal sample preparation [35][36][37].…”
Section: Introductionmentioning
confidence: 99%